1987
DOI: 10.1007/bf02074654
|View full text |Cite
|
Sign up to set email alerts
|

Potassium-induced histamine release from mast cells and its inhibition by ketotifen

Abstract: Potassium chloride induced a dose-dependent release of histamine from rat peritoneal mast cells at concentrations from 5 to 150 mM in the absence of extracellular Ca2+. Potassium concentrations greater than 150 mM produced less histamine release. The release was energy-dependent and was complete within one minute. The histamine liberating effect of KCl could be inhibited by NaCl and by preincubation with ketotifen. The monovalent cations, Rb+ and Cs+ also evoked histamine release, whereas Na+ and Li+ were inef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…On the other hand, ketotifen is one of the second-generation antihistamine drugs that exert anti-allergic effects primarily by antagonizing histamine H1 receptors [2]. However, later studies using human conjunctival mast cells additionally revealed a mast cell-stabilizing property of ketotifen [7,8], consistent with its higher potency in the treatment of allergic disorders. So far, by measuring the amount of chemokines released from rat peritoneal mast cells, such as histamine and β-hexosaminidase, previous studies have suggested the superiority of ketotifen to tranilast in the properties of mast cell stabilization [9][10][11].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…On the other hand, ketotifen is one of the second-generation antihistamine drugs that exert anti-allergic effects primarily by antagonizing histamine H1 receptors [2]. However, later studies using human conjunctival mast cells additionally revealed a mast cell-stabilizing property of ketotifen [7,8], consistent with its higher potency in the treatment of allergic disorders. So far, by measuring the amount of chemokines released from rat peritoneal mast cells, such as histamine and β-hexosaminidase, previous studies have suggested the superiority of ketotifen to tranilast in the properties of mast cell stabilization [9][10][11].…”
Section: Introductionmentioning
confidence: 96%
“…According to previous in vivo studies, the serum concentration of ketotifen ranges from 10 to 100 nM in humans when orally administered for the treatment of systemic allergic reactions [33,34]. However, in in vitro studies using rat peritoneal mast cells or human conjunctival mast cells, doses as high as 100 µM ketotifen were required to effectively elicit its inhibitory property on histamine release [7,8,35]. Since doses more than 1 mM were cytotoxic enough to cause membrane lysis [36], we tried doses starting from 1 µM up to 100 µM in the present study (Fig.…”
Section: Effects Of Tranilast and Ketotifen On Degranulation From Ratmentioning
confidence: 99%
“…Sneezing and rhinorrhea could be associated [40,41]. Severe dyspnea and upper airway obstruction may be caused by stings to the face [42][43][44][45][46].…”
Section: Local Symptomsmentioning
confidence: 99%
“…Our previous work showed a dose-dependent release of HA from rat peritoneal mast cells by 50 150 mM KC1 in the absence of extracellular Ca + + and a direct effect of K + on the mast cell membrane and its role in HA secretion have been suggested [1]. In order to obtain more data concerning the mechanism of K+-induced HA release fu mast cells, the effects of TEA and TMA have now been studied.…”
Section: Introductionmentioning
confidence: 95%
“…These compounds appeared to be potentially useful tools for studying the possible existence of K § channels in mast cells and their involvement in K § HA release. Rat peritoneal mast cells were obtained from male CFY rats (200-300 g) by washing the peritoneal cavity with buffered saline (PBS) containing NaC1 154 mM, KC1 2 mM, Na2HPO 4 10 mM, KH2PO 4 5mM, CaC12 lmM and MgC12 1raM as described previously [1]. After complete removal of PBS by centrifugation, cells were incubated in 500 gl of 10 mM HEPES buffer containing 150raM KC1 at 37~ for 10 rain.…”
Section: Introductionmentioning
confidence: 99%